Inhaled turmerones can be incorporated in the organs via pathways different from oral administration and can affect weight-gain of mice - Takemoto, Yuki; Kishi, Chihiro; Ehira, Hinano; Matsui, Nobutaka; Yamaguchi, Taichi; Yoshioka, Yuri; Matsumura, Shinichi; Moriyama, Tatsuya; Zaima, Nobuhiro (Scientific reports, 2022)
Turmerones (α-turmerone, β-turmerone, and ar-turmerone) are the major volatile compounds in turmeric ( Curcuma longa ), a perennial herb of the ginger family. We previously reported that inhaled volatile turmerones could be transferred in the blood and organs. However, the difference between the two pathways, oral administration and inhalation, and the effect of inhaled turmerones on biological activities remain unknown. In this study, we compared the distribution patterns of turmerones after oral administration and inhalation. The relative levels (concentrations of turmerones in each organ/serum) in the lung, olfactory bulb, brain, heart, kidney, and epididymal fat in the inhalation group tended to be, or are significantly, higher than in the oral administration group. The relative levels of brown adipose tissue in the inhalation group were lower than in the oral administration group. Long-term (50 days) inhalation to volatile turmerones suppressed weight gain and hypertrophy of adipocytes in the epididymal fat of mice fed a high-fat diet. These results suggest that inhaled turmerones can be incorporated into the organs of mice via different pathway from as to those from oral administration and can affect the biological function of the organs under certain conditions.